2020
DOI: 10.1002/ange.202005842
|View full text |Cite
|
Sign up to set email alerts
|

Carrier‐Induced Modification of Palladium Nanoparticles on Porous Boron Nitride for Alkyne Semi‐Hydrogenation

Abstract: Chemical modifiers enhance the efficiency of metal catalysts in numerous applications, but their introduction often involves toxic or expensive precursors and complicates the synthesis. Here, we show that a porous boron nitride carrier can directly modify supported palladium nanoparticles, originating unparalleled performance in the continuous semi‐hydrogenation of alkynes. Analysis of the impact of various structural parameters reveals that using a defective high surface area boron nitride and ensuring a pall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Therefore, the strong host–guest electronic interaction between Pd and interstitial boron is thought to be more substantial than that caused by lattice expansion for changing the electronic structure and influencing the adsorption of cis-hexen-1-ol for the stereoselective partial hydrogenation of 3-hexyn-1-ol. Pérez-Ramírez and co-workers suggested that the incorporation of interstitial boron to the palladium subsurface on a porous boron nitride-supported palladium catalyst creates the suitable active ensembles that increase the selectivity for the semihydrogenation of 1-hexyne . In addition to boron, the surface/subsurface modification of palladium by other p -block hybrid atoms including sulfur and phosphorus can also affect the adsorption behavior of reactants, changing the catalytic activity and selectivity. The incorporation of sulfur into the palladium lattice leads to the formation of a nanostructured Pd 3 S phase with exposure to the (202) plane.…”
Section: Omc-supported Metals and Metal Oxides For Heterogeneous Cata...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the strong host–guest electronic interaction between Pd and interstitial boron is thought to be more substantial than that caused by lattice expansion for changing the electronic structure and influencing the adsorption of cis-hexen-1-ol for the stereoselective partial hydrogenation of 3-hexyn-1-ol. Pérez-Ramírez and co-workers suggested that the incorporation of interstitial boron to the palladium subsurface on a porous boron nitride-supported palladium catalyst creates the suitable active ensembles that increase the selectivity for the semihydrogenation of 1-hexyne . In addition to boron, the surface/subsurface modification of palladium by other p -block hybrid atoms including sulfur and phosphorus can also affect the adsorption behavior of reactants, changing the catalytic activity and selectivity. The incorporation of sulfur into the palladium lattice leads to the formation of a nanostructured Pd 3 S phase with exposure to the (202) plane.…”
Section: Omc-supported Metals and Metal Oxides For Heterogeneous Cata...mentioning
confidence: 99%
“…Peŕez-Rami ́rez and co-workers suggested that the incorporation of interstitial boron to the palladium subsurface on a porous boron nitride-supported palladium catalyst creates the suitable active ensembles that increase the selectivity for the semihydrogenation of 1hexyne. 169 In addition to boron, the surface/subsurface modification of palladium by other p-block hybrid atoms including sulfur and phosphorus can also affect the adsorption behavior of reactants, changing the catalytic activity and selectivity. 170−172 The incorporation of sulfur into the palladium lattice leads to the formation of a nanostructured Pd 3 S phase with exposure to the (202) plane.…”
Section: Effect Of Electronic Structuresmentioning
confidence: 99%
“…The incorporation of boron into palladium as an interstitial lattice structure has been considered previously for enhancing the selectivity in alkyne hydrogenation, as an alternative to Lindlar's catalyst. [21,[39][40][41][42][43] As part of the that study, Chan investigated the stability of the PdB x phase as a function of temperature and gas atmosphere. [21] Whilst PdB x was formed and tested under different conditions on a different sample, the grouping of boron, carbon and nitrogen in the periodic table, and the conclusions that might be drawn from comparing the three, should not be ignored.…”
Section: Stability Comparisonmentioning
confidence: 99%
“…Benefiting from features such as a high surface area, a priori tunable chemistry and porosity, and high thermal stability, porous BN has recently attracted interests for various applications such as molecular storage and separation, 4–9 catalysis (incl. photocatalysis), 10–13 and drug delivery. 14…”
Section: Introductionmentioning
confidence: 99%
“…Beneting from features such as a high surface area, a priori tunable chemistry and porosity, and high thermal stability, porous BN has recently attracted interests for various applications such as molecular storage and separation, [4][5][6][7][8][9] catalysis (incl. photocatalysis), [10][11][12][13] and drug delivery. 14 Chemical functionalisation can help tune the adsorptive, catalytic and optoelectronic properties of porous BN, all of which are relevant to the applications mentioned above.…”
Section: Introductionmentioning
confidence: 99%